Kipper and the Giant Supplementary Reading Material - Roderick Hunt; Roderick Hunt (Oxford Reading Tree, 2012)
This story is about a magic key which glows and Kidnappers who kidnaps famous bears. The key turns Kipper into a teddy bear . Kidnappers were actually bears. He gave them honey and saved the famous bears. He went home and shared his dream with Biff and Chip, they didn't believe Kipper.